(untitled) (Research, Society and Development, 2021)
Klebsiella pneumoniae (gram negative and immobile bacteria) is found in the intestinal tract of mammals. When an imbalance occurs, the bacteria multiply intensely, causing infectious diseases. Therefore, the objective of the article is to correlate the prevalence of animal isolates, with the existing microbiota in the hands of the owners, warning about the risk of cross-transmission. 114 dogs were used to collect samples, performed at different anatomical sites and on the owner’s hands, using sterile swabs moistened in 2 mL phosphate buffered saline solution (PBS) placed in a test tube. Subsequently, 0.1 mL of each dilution was cultured on the MacConkey agar plates incubated under aerobic conditions at 37 ° C for 24 hours. Then, biochemical tests and chromogenic agar were used to screen suspected samples of Klebisiella spp. and the definitive identification was performed using mass spectrophotometry. 456 samples were collected from 114 dogs from various anatomical sites between animals and guardians. Of the 456 samples, 70 (15.35%) showed characteristics similar to Klebsiella spp after screening in biochemical tests and in Chromagar. Regarding the number of samples, of the 70 suggestive of Klebsiella, 9 samples (12.85%) were confirmed. with the present study, the presence of Klebsiella pneumoniae was confirmed in eight dogs and one guardian. And it was found that more studies are needed to unveil the possibility of transmission, as well as the mechanism for it to occur.